Exertional heat illness: adoption of policies and influencing contextual factors as reported by athletic administrators - Scarneo-Miller, Samantha E.; Adams, William M.; Coleman, Kelly A.; Lopez, Rebecca M. (Sports Health, 2023)
Background:Little is known about the adoption by athletic administrators (AAs) of exertional heat illness (EHI) policies, and the corresponding facilitators and barriers of such policies within high school athletics. This study describes the adoption of comprehensive EHI policies by high school AAs and explores factors influencing EHI policy adoption.Hypothesis:We hypothesized that <50% of AAs would report adoption of an EHI policy, and that the most common facilitator would be access to an athletic trainer (AT), whereas the most common barrier would be financial limitations.Study Design:Cross-sectional.Level of Evidence:Level 4.Methods:A total of 466 AAs (82.4% male; age, 48 ± 9 years) completed a validated online survey to assess EHI prevention and treatment policy adoption (11 components), as well as facilitators and barriers to policy implementation. Access to athletic training services was ascertained by matching the participants? zip codes with the Athletic Training Locations and Services Project. Policy adoption, facilitators, and barriers data are presented as summary statistics (proportions, interquartile range (IQR)). A Welch t test evaluated the association between access to athletic training services and EHI policy adoption.Results:Of the AAs surveyed, 77.9% (n = 363) reported adopting a written EHI policy. The median of EHI policy components adopted was 5 (IQR = 1,7), with only 5.6% (n = 26) of AAs reporting adoption of all policy components. AAs who had access to an AT (P = 0.04) were more likely to adopt a greater number of EHI-related policies, compared with those without access to an AT. An AT employed at the school was the most frequently reported facilitator (36.9%).Conclusion:Most AAs reported having written EHI policy components, and access to an AT resulted in a more comprehensive policy.Clinical Relevance:Employment of an AT within high school athletics may serve as a vital component in facilitating the adoption of comprehensive EHI policies.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

Athletic training employment in secondary schools by geographic setting and school size within the United States. - Suzuki-Yamanaka, Miwako; Huggins, Robert A.; Armstrong, Kirk J.; Coleman, Kelly A.; Casa, Douglas J.; Kaneoka, Koji (Journal of athletic training, 2021)
Context: The Athletic Training Locations and Services (ATLAS) Annual Report suggested that athletic trainer (AT) employment status differed based on geographic locale. However, the influence of geographic locale and school size on AT employment is unknown. Objective: To determine if differences existed in the odds of having AT services by locale for public and private schools and by student enrollment for public schools. Design: Cross-sectional study. Setting: Public and private secondary schools with athletics programs. Patients or Other Participants: Data from 20 078 US public and private secondary schools were obtained. Main Outcome Measures(s): Data were collected by the ATLAS Project. Athletic trainer employment status, locale (city, suburban, town, or rural) for public and private schools, and school size category (large, moderate, medium, or small) only for public schools were obtained. The employment status of ATs was examined for each category using odds ratios. Logistic regression analysis produced a prediction model. Results: Of the 19 918 public and private schools with available AT employment status and locale, suburban schools had the highest access to AT services (80.1%) with increased odds compared with rural schools (odds ratio = 3.55 [95% CI = 3.28, 3.85]). Of 15 850 public schools with known AT employment status and student enrollment, large schools had the highest rate of AT services (92.1%) with nearly 18.5 times greater odds (odds ratio = 18.49 [95% CI = 16.20, 21.08]) versus small schools. The logistic model demonstrated that the odds of access to an AT increased by 2.883 times as the school size went up by 1 category. Conclusions: Nationally, suburban schools and large public schools had the greatest access to AT services compared with schools that were in more remote areas and with lower student enrollment. These findings elucidate the geographic locales and student enrollment levels with the highest prevalence of AT services. Ó by the National Athletic Trainers’ Association, Inc
1 citations (Crossref) [2023-10-31] https://www.ncbi.nlm.nih.gov/pubmed/33480996 ; https://pubmed.ncbi.nlm.nih.gov/33480996/ ; https://meridian.allenpress.com/jat/article/56/9/1010/451538/Athletic-Training-Employment-in-US-Secondary ; https://europepmc.org/article/MED/33480996
Keywords: adult; article; athletic trainer; athletics; controlled study; cross-sectional study; dept.hms; employment status; female; high school; human; male; outcome assessment; peer-reviewed; prediction; prevalence; training

Spinal cord injury management policies in high school sports as reported by athletic administrators - Scarneo-Miller, Samantha E.; Swartz, Erik E.; Register-Mihalik, Johna K.; Coleman, Kelly A.; Emrich, Christina M.; DiStefano, Lindsay J. (Translational Journal of the American College of Sports Medicine, 2024)
Introduction/Purpose Athletic administrators (AA) in U.S. high schools are uniquely positioned to provide guidance and endorsement for the prevention and management of common sport-related catastrophic injuries, such as the development of a spinal cord injury management (SCIM) policy. The purpose of this project was to evaluate AA’s knowledge of comprehensive SCIM policies in U.S. high schools. Secondarily, we aimed to investigate the factors, facilitators, and barriers to the development and adoption of comprehensive policies. Methods An online questionnaire was distributed to 6423 AA working in U.S.-based high school athletics, with 366 included in the final data analysis. The questionnaire evaluated AA’s knowledge of comprehensive SCIM policies addressing components of adoption, documentation, and communication. The questionnaire was developed based on the 2002 “National Athletic Trainers’ Association Position Statement: Acute Management of the Cervical Spine-Injured Athlete.” The questionnaire also inquired about facilitators and barriers to developing and adopting comprehensive policies. Proportions were calculated for policy adoption, and independent-samples t-tests evaluated the influence of athletic training services on comprehensive SCIM policies. Results About half of AA (49.2%, n = 180/366) reported having all recommended components of a written SCIM policy. AA who had access to an athletic trainer (yes = 62.9%, no = 18.1%, unknown = 19%) were more likely to have a comprehensive SCIM policy compared with those without access (80.6% vs 19.4%, χ21 = 7.091, P = 0.008, prevalence ratio = 1.24, 95% confidence interval = 1.03–1.50). The most commonly reported facilitator (49.9%) was “having a medical professional at the school,” and the main barrier (30.2%) was “my school would need more information, resources, assistance, etc.” Conclusions The findings identify areas for improvement in supporting the health and safety of children in high school participating in interscholastic athletics. Future dissemination and implementation research should develop strategies tailored to individual school community and need to improve SCIM policy adoption and implementation.
Keywords: dept.hms